HRM w Grupie LUKAS - ocena skuteczności wdrożenia i upowszechnienia - Zając, Czesław (HRM in LUKAS Group - the Evaluation of the Implementation Effectiveness, 2006)
HRM implementation in LUKAS Group has been presented in this paper. There was described at the beginning the personal function in realized LUKAS S.A. until the time of building up LUKAS Bank S.A. Then changes in the areas of evaluating, motivating, training and development of personnel have been shown, as a framework for the complex and professional HRM system in these companies. These changes have been described in the following dimensions: strategic, operational, organizational and structural. The analysis of the method of this implementation and social, psychological, organizational and technological barriers, restricting this implementation, has been done as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 535-541